(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The paper analyzes the role of Clinical Ethics Committees in evaluating requests for medical assistance in dying (MMA), in light of the case law of the Italian Constitutional Court and the organizational choices adopted by the Emilia-Romagna Region. Starting from ruling no. 242/2019, which identifies the territorially competent ethics committees as the third-party body responsible for verifying the existence of the requirements for access to the AMM, the paper reconstructs the doctrinal debate regarding the identification of these bodies, focusing in particular on the distinction between Ethics committees for experimentation and Committees for ethics in the clinic. This paper examines Emilia-Romagna’s decision to assign the evaluation function to the Regional Committee for Clinical Ethics (COREC), established in 2024 as an evolution of the experience gained with the Committee for Clinical Ethics of the AUSL-IRCCS of Reggio Emilia. The paper illustrates the regional organization of ethics committees, the Technical-Operational Instructions for Access to the AMM, and the specific role of COREC in the process, characterized by a mandatory but non-binding ethical assessment, subsequent to the medical-clinical one. Drawing on the evidence emerging from the CEC experimental project and the experience gained by COREC in the first two years of activity, the paper argues how the Clinical Ethics Committees represent the most suitable bodies to ensure adequate protection of personal vulnerability, support for complex end-of-life decision-making processes and care that respects the patient’s values and dignity. In conclusion, the paper emphasizes the value of ethics counseling in AMM’s journey and calls for regulatory regulation of clinical ethics committees, as well as strengthening the bioethics training of healthcare professionals involved in end-of-life care.